A cognitive linguistic study of cultural models of age in American English and Egyptian Arabic: A corpus-based approach - Said, Hebatallah (AUC Knowledge Fountain, 2017)
The role of cultural models in sharing social knowledge, shaping social practices and organizing the perceptions, motivations and actions of community members is widely discussed in the literature (Holland & Quinn, 1987; Watson-Gegeo & Gegeo, 1999; Fryberg & Markus, 2007; Curwood, 2014). In each culture, there are perceptions that indicate what is appropriate or inappropriate according to a person's age (Jensen, 2014). This descriptive and exploratory study examines the Egyptian and American force dynamic cultural models of age from a cognitive linguistics approach. As cognitive linguistics applies a usage-based approach to language, this study relies on naturally occurring data derived from two different types of corpora. For the American English sample (n=200), the web-based corpus GLOWBE was utilized. To reach an equally authentic and rich sample, Web-as Corpus was utilized for the Egyptian Arabic sample (n=179). The findings of the study showed that Egyptians view age in general as a strong blocking force, while the American culture views old age to be a strong force, one that lets more than it blocks. Moreover, the Egyptian culture was found to hold a number of age-related force dynamic cultural models that govern social interaction, unlike the American culture, which holds a number of force dynamic cultural models that tie age with cognitive skills. The study also revealed some cultural models that are undergoing change; these include OLD AGE BLOCKS HAVING SPOUSE OF CHOICE in the Egyptian culture and OLD AGE BLOCKS PARENTING in the American culture. The study also revealed more similarities between the Egyptian and American age-related cultural models pertaining to engaging in meaningful relationships than those pertaining to understanding and wisdom. The study concludes by hypothesizing a framing image schema of AGE IS A PATH in both the Egyptian and American culture.